Human Resource Architecture Transformation Case Study in Construction Company - Wikumurti; Muchlis R. Luddin; Thomas Suyatno (IJHCM (International Journal of Human Capital Management), 2019)
This study focuses on the transformation of the architecture of human resource construction services companies into toll road development companies, to get the right model in the implementation of the Human Resources system towards employee engagement and satisfaction which is reflected in the improvement of company performance. The study used a qualitative approach through case studies in construction service companies with data collection methods using observation, interviews, document observation and surveys of company employees by questionnaire. Research informants are the management of the Human Resources construction services company. The results of the case study show that the implementation of a human resource system in a company that is transformed from a construction services company to a toll road development company includes establishing the company's vision and mission from a construction company to a toll road developer, changing company organizations from a construction services business organization to a road development organization toll road, employee recruitment system, employee development and training, career management, reward system and termination / retirement system have been well applied in the process of transformation from construction service companies to toll road development companies. This has an effect on increasing the value of employee engagement and satisfaction and is reflected in the improvement of the company's performance over the past 4 years from 2015 to 2018.